P714 Efficacy and safety of infliximab retreatment in luminal Crohn's disease: a multi-centre, prospective, observational cohort (REGAIN) study. (25th January 2019) - Boschetti, G; Pariente, B; Laharie, D; Roblin, X; Gilletta, C; Aubourg, A; Bourreille, A; Zallot, C; Hebuterne, X; Buisson, A; Grimaud, J-C; Bouhnik, Y; et al.
Abstract: Background: Although the therapeutic arsenal in Crohn's disease (CD) is expanding, reintroducing an anti-TNF treatment previously discontinued is still questionable. Data on retreatment after intolerance or loss of response remain controversial. The objective of this study was to describe the efficacy and safety of infliximab (IFX) reintroduction in luminal CD after stopping for loss of response or intolerance. Methods: We conducted a prospective multi-centre observational cohort study including adult patients with active luminal CD in whom IFX therapy was reintroduced after at least 6 months of discontinuation. The reasons for the initial discontinuation of IFX could be a loss of efficacy after an initial response in a patient treated for at least 6 months (secondary loss of response) or intolerance to IFX regardless the previous duration of treatment. At baseline, patients had a clinically (CDAI>150) and objectively active CD (C-reactive protein level> 5 mg/l and/or faecal calprotectin>250 μg/g and/or endoscopic activity and/or radiological activity). The reintroduction schedule included three IFX infusions at weeks 0, 4, and 8, after a systematic premedication. Maintenance treatment was administered every 8 weeks. The primary endpoint was the efficacy of IFX retreatment at Week 26 defined by a CDAI < 150 in the absence of IFX discontinuation or use of corticosteroid therapy, surgery, or other biologic. Efficacy and tolerance of IFX retreatment were evaluated over a 12-month period. Results: From June 2015 to June 2018, 96 patients were included in 16 centres. Reasons for the initial discontinuation of IFX were secondary loss of response in 47 patients (49%), intolerance in 21 patients (22%) and other reasons in 28 patients (29%). At Week 26, 34 patients (35%) reached the primary endpoint. No significant difference was observed between rates of clinical remission at Week 26 in patients with initial secondary loss of response and those with IFX intolerance (38% and 33%, p = 0.9, respectively). Thirty-seven patients (36%) had an intolerance reaction to retreatment with IFX on average after 3 infusions, requiring drug discontinuation in 31 (30%) cases. Optimisation of IFX treatment by increasing doses and/or frequency of infusions was necessary in 45 patients (47%) during the 12-month follow-up period. Nor the presence of anti-drug antibodies at baseline neither IFX trough level at Week 8 were predictive of IFX retreatment failure. Conclusions: IFX retreatment is safe and efficient in more than one third of CD patients regardless the reason of prior discontinuation (loss of response or intolerance). Early pharmacokinetics at retreatment cannot predict subsequent IFX intolerance or failure at retreatment.